A surgical approach to schwannomas originating from the esophageal branch of the recurrent laryngeal nerve: Pictorial essay. Issue 11 (20th August 2019) - Kobayashi, Kenya; Matsumoto, Yoshihumi; Matsumoto, Fumihiko; Sato, Tetsufumi; Mori, Taisuke; Tsuchida, Takaaki; Omura, Go; Matsumura, Satoko; Ikeda, Atsuo; Sakai, Azusa; Eguchi, Kotaro; Yoshimoto, Seiichi
Abstract: Background: Schwannoma originating from the esophageal branch of the recurrent laryngeal nerve is clinically rare event. The best approach to preoperative pathological diagnosis, surgery, and airway management for this submucosal tumor in the tracheal membranous portion remains controversial. Methods and Results: A 69‐year‐old man had developed dyspnea for 6 months. Transnasal endoscopy revealed a submucosal tumor in the tracheal membranous portion, obstructing the airway. CT revealed that the tumor was located between the trachea and esophagus. Needle biopsy using ultrasonic bronchoscope diagnosed the submucosal tumor as schwannoma. Intercapsular resection was performed by a transtracheal approach under local anesthesia. The tumor was completely resected and the patient's symptoms completely improved. Conclusions: We report the treatment of a rare schwannoma originating from the esophageal branch of the recurrent laryngeal nerve. A needle biopsy using an ultrasonic bronchoscope was successfully used for diagnosis. Intercapsular resection by a transtracheal approach was effective.